STROKE IN ELDERLY; IDENTIFICATION OF RISK FACTORS - ANSARI, ASMAT KAMAL; AKHUND, ISRAR AHMED; SHAIKH, ABDUL QADIR (Journal of Ayub Medical College Abbottabad, 2001)
Background: This study was undertaken to identify stroke risk factors prevalent in our elderly population. Methods: The subjects included 100 consecutive stroke patients with recent stroke, at or above the age of fifty years, both sexes inclusive, who presented at medical units of Liaqat Medical College Hospital Hyderabad. A detailed history of the patients was taken, thorough clinical examination was done and various laboratory tests were carried out to identify all the possible risk factors for stroke in the subjects. Results: Most important risk factors prevalent in our population were found to be hypertension (64%), diabetes mellitus (29%), smoking (29%), heart disease (23%), obesity (17%) and hypercholesterolemia (15%). Conclusion: It is concluded that in elderly stroke patients, many risk factors are identified. Awareness of these risk factors, their early and effective treatment and adaptation of various preventive measures is warranted.